The state of the Arctic - Finger, Matthias (Arctic Portal, 2011)
Professor Matthias Finger, EPFL - the Ecole Polytechnique Fédérale de Lausanne, Switzerland, talks here in the NRF 6th open assembly in Hveragerði, Iceland, in September of 2011. Please click on the link above to see the video.